2011
DOI: 10.1007/s00264-011-1363-y
|View full text |Cite
|
Sign up to set email alerts
|

Results of forty two computer-assisted double level osteotomies for severe genu varum deformity

Abstract: Purpose The goal of this article was to present the clinical and radiological results of 42 severe genu varum operated on between August 2001 and June 2010 using computer navigation. Methods All the osteotomies were navigated using the Orthopilot® device (B-Braun-Aesculap, Tuttlingen, Germany). The procedure was performed such that after inserting the rigid bodies and calibrating the lower leg, we first made the femoral closing wedge osteotomy (from four to seven mm) which was fixed by an AO T-Plate, and then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
2
41
0
9
Order By: Relevance
“…Most of the previous studies that compared the results of navigated HTO with those after the conventional method reported that the navigated group achieved more accurate coronal alignment with less frequent outliers than the conventional group [10][11][12][13][14][15][16]. However, a concerning incidence of outliers is still reported even in navigated HTO, with a wide range, from 0 to 35 % [7,10,12,[14][15][16][17]. Whether the use of navigation improves sagittal alignment is still controversial [11][12][13]18].…”
Section: Introductionmentioning
confidence: 96%
“…Most of the previous studies that compared the results of navigated HTO with those after the conventional method reported that the navigated group achieved more accurate coronal alignment with less frequent outliers than the conventional group [10][11][12][13][14][15][16]. However, a concerning incidence of outliers is still reported even in navigated HTO, with a wide range, from 0 to 35 % [7,10,12,[14][15][16][17]. Whether the use of navigation improves sagittal alignment is still controversial [11][12][13]18].…”
Section: Introductionmentioning
confidence: 96%
“…In our series based on 42 computer-assisted cases, 20 we had no complication but one case of recurrence of the deformity related to an impaction of the femoral osteotomy on the medial side (high body mass index patient). Two patients were lost to follow-up after removing of the plates (24 months) but were included in the results because the file was complete at that date.…”
Section: Resultsmentioning
confidence: 83%
“…One from Babis et al in 2002 13 and one from our group. 20 In their article, Babis et al 13 reported on 24 patients (29 knees) operated up on using a conventional technique (two closing wedge osteotomies). The mean preoperative HKA angle was 193.3 degrees (i.e., 13.3 degrees of varus), and they used a computer-aided analysis of the mechanical axes of the knee for preoperative planning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further prospective studies are needed to confirm that the use of CAS is justified, since it increases surgical duration and navigation equipment comes at significant additional cost. Computer navigation may also have a role in aiding more complex osteotomies, such as following femoral malunion [82] or combined femoral and tibial osteotomies for severe genu varum [83].…”
Section: Clinical Outcomesmentioning
confidence: 99%